Direct RNA sequencing enables improved transcriptome assessment and tracking of RNA modifications for medical applications - Hewel, Charlotte; Wierczeiko, Anna; Miedema, Johannes; Friedrich, Johannes; Hofmann, Felix; Weißbach, Stephan; Dietrich, Vincent; Holthöfer, Laura; Haug, Verena; Mündnich, Stefan; Schartel, Lukas; Lehmann, Lioba; et al. (Nucleic acids research, 2025)
Direct RNA sequencing (DRS) is a Nanopore-based technique for analyzing RNA in its native form. This technique promises breakthroughs in diagnostics and biomarker development. Coupled to RNA002 sequencing chemistry, its clinical implementation has been challenging due to low throughput, low accuracy, and lack of large-scale RNA-modification models. In this study, we evaluate the improvements achieved by pairing the latest RNA004 chemistry with novel modified-base-calling models for pseudouridine and N6-methyladenosine using diverse RNA samples from cell lines, synthetic oligos, and human blood. Finally, we present the first clinical application of DRS by confirming the loss of RNA methylation in a patient carrying truncating mutations in the methyltransferase METTL5. Conclusively, the combined use of RNA004 chemistry with the base-calling models significantly improved the throughput, accuracy, and site-specific detection of modifications. From this perspective, we offer an outlook on the potential suitability of DRS for use in routine diagnostics, as well as the first comprehensive benchmark of human peripheral blood. Furthermore, we demonstrate on the basis of a stop-codon readthrough enhancing agent potential roadblocks for routine quality assessments of RNA therapeutics.
Gesehen am 29.01.2026